Childhood trauma and suicide risk in hospitalized patients with schizophrenia: the sequential mediating roles of pandemic related post-traumatic stress symptoms, sleep quality, and psychological distress - Xie, Min; Zou, Xuemin; Xie, Yingjing; Hu, Li; Tang, Yiguo; Cai, Jai; Kuang, Yunxue; Zhu, Ling; Zou, Min; Wang, Qiang (Frontiers in Psychiatry, 2023)
Stressful global situation due to the COVID-19 pandemic caused a tremendous impact on mental health in hospitalized patients with schizophrenia. The mediating roles of psychological impact related to COVID-19, sleep quality, and psychological distress were investigated in the association between childhood trauma and suicidal risk in hospitalized patients with schizophrenia.We analyzed cross-sectional data of 147 patients with schizophrenia and 189 healthy controls (HCs).Results: Histories of childhood trauma and schizophrenia were good predictors of COVID-19-related psychological impact, global sleep quality, and psychological distress. Moreover, the series mediation model showed that the effect of childhood trauma on suicidal risk in hospitalized patients with schizophrenia was totally sequential mediated by the psychological impact of COVID-19, sleep quality, and psychological distress.Clinicians need to recognize the increased suicidal risk associated with COVID-19related psychological distress in schizophrenia patients with a history of childhood trauma.